Research Variable Measurement Model with Second Order Factor and First Order Factor - Kuncoro, Amin; Samekto, Agus Aji; Pamungkas, Fajar (Global Health Science Group, 2023)
The study aims to explain the extent of the role of constructs that arise from factor analysis conducted by researchers on some of the lowest factors or constructs. Factor analysis is an initial that can be identified from several variables that are grouped into higher factors so that they are referred to as second order factors. This research is a research with the latest reference-based literature review approach from research methodology books. The second order factor allows researchers to simplify a model by combining several interrelated constructs. These variables are complex to be understood by the researcher and make interpretations of the analyzed results. In contrast to the first order factor, the construct that arises from the collection of variables is then measured and identified as the lowest factor in the level of factor hierarchy from the analysis.